Evaluation on current status of soil quality under agroforestry practices : a case study on Sabal forest reserve, Sarawak - Mimi Sophia, Binti Sarbandi. (2002)
Five land use types in the Sabal Forest Reserve reprensting the agroforestry practices termed as rubber planting, mulitlayer cropping, intercropping forest plantation and wildlife breeding, respectively were studied in comparison with the old forest as the extrapolated area examined at surface soil (0-10cm) and subsurface soil (10-20cm). The soils fromrespective land use types were sampled based on the soil parameters (pH Cation Exchange Capacity (CEC), exchangeable cations (Ca, Mg, K and Na), organic matter (OM), available phosphorus (P), total carbon (C), sulfur (S) and nitrogen (N) as well as moisture content. Based on the objectives, one soil type namely the nyalau Series has been compared together with the previous study with the oil forest.